Constructing purchasing power parities using a reduced information approach a research study. (Metro Manila, Philippines Asian Development Bank, 2020)
The approach can generate more firmly based estimates of PPPs, price level indexes, and measures of real (PPP-based) expenditures than conventional extrapolation methods. The results include PPP-based gross domestic product and its major aggregates of individual consumption expenditure by households and nonprofit institutions serving households, government final consumption expenditure, gross fixed capital formation, changes in inventories and acquisitions less disposals of valuables, and balance of exports and imports.
Keywords: Economics; Electronic books